The search for the missing bones - Moore, Eva.; Enik, Ted; Cole, Joanna (New York : Scholastic, 1999)
Ms. Frizzle's students find out why their skeleton costumes are all missing different bones, and learn about the skeletal system.
"Based on The magic school bus books written by Joanna Cole and illustrated by Bruce Degen"--T.p. verso.
Accelerated Reader AR
Keywords: Skeleton -- Juvenile fiction; Bones -- Juvenile fiction; Schools -- Juvenile fiction